2015
DOI: 10.1021/acs.jpcc.5b04411
|View full text |Cite
|
Sign up to set email alerts
|

Biomorph Oscillations Self-organize Micrometer-Scale Patterns and Nanorod Alignment Waves

Abstract: The coprecipitation of barium carbonate and silica spontaneously creates complex micrometer-scale objects such as sheets and helices. These structures consist of densely packed crystalline nanorods that in the case of sheets align in radial direction. We report the existence of an additional level of self-organization that creates oscillatory height variations in biomorph sheets. These topographic features take the form of either concentric rings or disordered, patchy patterns and form immediately in the wake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 43 publications
7
32
0
Order By: Relevance
“…The outer layers of the rod‐shaped particles appear wider, possibly due to a geometric effect of the cross‐sections cutting through the ellipsoidal rod‐shaped particles at different distances with respect to their centre ( e.g ., Cosmidis et al., ). Similar nanometre scale autocatalytic self‐organization of the precipitates, due to oscillations in the local microenvironment, is known in silica‐carbonate biomorphs ( e.g ., Nakouzi, Ghoussoub, Knoll, & Steinbock, ), and can result in the formation of intrinsic mineralized banding patterns with the same periodicity (Montalti et al., ). Therefore, such layering observed in rod‐shaped apatite particles could be the result of alternating levels of phosphate input, in turn, a result of intermittent microbial phosphate pumping by polyphosphate‐accumulating bacteria (Jones, Flood, & Bailey, ; Schulz & Schulz, ).…”
Section: Discussionmentioning
confidence: 99%
“…The outer layers of the rod‐shaped particles appear wider, possibly due to a geometric effect of the cross‐sections cutting through the ellipsoidal rod‐shaped particles at different distances with respect to their centre ( e.g ., Cosmidis et al., ). Similar nanometre scale autocatalytic self‐organization of the precipitates, due to oscillations in the local microenvironment, is known in silica‐carbonate biomorphs ( e.g ., Nakouzi, Ghoussoub, Knoll, & Steinbock, ), and can result in the formation of intrinsic mineralized banding patterns with the same periodicity (Montalti et al., ). Therefore, such layering observed in rod‐shaped apatite particles could be the result of alternating levels of phosphate input, in turn, a result of intermittent microbial phosphate pumping by polyphosphate‐accumulating bacteria (Jones, Flood, & Bailey, ; Schulz & Schulz, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the planar structures start from a globule on the reactor substrate and then grow on that surface radially outwards at speeds of a fraction of to a few micrometers per minute (Figure a) ,. These sheets can be surprisingly circular, but typically experience disruptions of the growth front.…”
Section: Biomorph Zoomentioning
confidence: 94%
“…In shallow solution layers, the typical pH ranges from 10 to 11 for this procedure and produces worms, double helices, and leaves. [10,16,24] However, in deeper containers and at higher barium concentrations, the pH can be extended to values of up to 11.8 producing stemmed flowers and coral-like shapes. [25] Noorduin et al demonstrated that temporary increases of the ambient CO 2 pressure (by opening and closing of the lid) induce thickened rings around the growing structures due to the faster formation of barium carbonate crystals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations